Assessment of health level and socio-economic characteristics of people working in the shipbuilding industry: a control group study - Koulouri, Agoritsa; Roupa, Zoe; Sarafis, Pavlos; Hatzoglou, Chryssi; Gourgoulianis, Konstantinos (My University, 2015)
The health level of the population and the way people perceive it has been associated with their physical and mental health, as well as with their social and occupational characteristics.
Keywords: Work; Health; Sickness absence